The Application of the Cooperative Integrated Reading and Composition (CIRC) Learning Model in Improving the Ability to Find Elements of the Nonfiction Book for Class VII Students of SMP Negeri 1 Ma'u Nias Regency 20202021 Learning Year - Maskaryanis Telaumbanua (Indonesian Journal of Education and Mathematical Science, 2021)
Reading is the process of obtaining information through writing. By reading, someone will add insight. The message conveyed by the author will be a consideration for the reader because in the discourse there is information that attracts readers. The more often you read, the more knowledgeable someone will be. Reading in education is one aspect of language skills that students need to master because reading is an important skill to support the learning process. This is because reading is the first step in understanding a subject matter. Through reading, students can absorb the information and ideas in reading. The objectives of this study were: To improve the ability to find elements of non-fiction books using the Cooperative Integrated Reading and Composition (CIRC) Learning Model for seventh grade students of SMP Negeri 1 Ma'u Nias Regency 2020/2021 Learning Year.